Application of a Humanistic Existential Counseling Approach to Reducing Adolescents' Anxiety for the Spiritual Future - Sulistyani; Syarifah Lubis; M. Irfan Khalifaur; Gusman Lesmana (PT FORMOSA CENDEKIA GLOBAL, 2023)
Adolescence is a transitional period between the life of children and the life of adults which is characterized by biological and psychological growth and development. The future is a mystery to everyone, no one knows what will happen in the future. With the uncertainty, not a few individuals feel anxious. The assessment method uses interviews, observation, and individual counseling services. The client is a 22-year-old woman who is experiencing future anxiety because she has made a mistake that God considers unforgivable. The approach technique used is humanistic existential counseling with the aim of helping clients reduce anxiety about their future. The result of this approach in service is a decrease in adolescent anxiety regarding the future.